THE EFFECT OF GENOTYPE QUALITY OF UNPAD SWEET CORN SEEDS TOWARDS ITS PHYSIOLOGICAL QUALITY - Niki Rahayu; Anne Nuraini; Sumadi Sumadi (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2018)
This study was aimed at determining the effect of genotype quality of Unpad sweet corn seeds on physiological quality after four months of storage. The experimental design used was a completely randomized design with a treatment factor of 16 genotypes of sweet corn with 2 replications. The data were analyzed using the F test, if there was a significant difference in Scott Knott’s test at the level of 5%. All of the seed genotypes had different qualities, so there was a significant difference in 100 grain weight parameters, germination and simultaneous growth based on ANOVA test. Seeds that had good initial physical quality are able to maintain quality until the end of storage period. After the storage period there is the best genotype, namely with code 613 which is able to maintain its physical-physiological quality until the end of storage. Based on the results of the study, it can be concluded that the genotype of sweet corn seed npad Genotype 613 (P5 x P1 (x) (3)) has good physical and physiological qualities and can be used as a candidate for hybrid elders. This is seen from the quality of seeds that meet the requirements of quality seed characters from 100 grain weight parameters and germination.PENGARUH MUTU GENOTIP BENIH JAGUNG MANIS UNPAD TERHADAP MUTU FISIOLOGISPenelitian ini bertujuan untuk mengetahui pengaruh mutu genotip benih jagung manis Unpad terhadap mutu fisiologis setelah empat bulan penyimpanan. Rancangan percobaan yang digunakan yaitu Rancangan Acak Lengkap dengan faktor perlakuan 16 genotipe jagung manis dengan 2 ulangan. Data dianalisis menggunakan uji F, apabila terdapat perbedaan yang signifikan dilakukan uji lanjut Scott Knott taraf 5 %.Semua genotip benih memiliki mutu yang berbeda, sehingga terdapat perbedaan yang signifikan pada parameter bobot 100 butir, daya berkecambah dan keserempakan tumbuh berdasarkan uji anova. Benih yang memiliki mutu fisik awal yang baik mampu mempertahankan mutu sampai periode akhir penyimpanan. Setelah periode simpan terdapat genotip terbaik yaitu dengan kode 613 yang mampu mempertahankan mutu fisik-fisiologisnya sampai akhir penyimpanan. Berdasarkan hasil penelitian dapat diambil kesimpulan bahwa genotip benih jagung manis Unpad Genotip 613 (P5 x P1 (x) (3)) memiliki mutu fisik dan fisiologis yang baik dan dapat dijadikan sebagai calon tetua hibrida. Hal ini dilihat dari kualitas benih yang memenuhi syarat karakter benih bermutu dari parameter bobot 100 butir dan daya berkecambah.